Tetramethylpyrazine: A promising drug for the treatment of pulmonary hypertension. (27th April 2020) - Chen, Yuqin; Lu, Wenju; Yang, Kai; Duan, Xin; Li, Mengxi; Chen, Xiuqing; Zhang, Jie; Kuang, Meidan; Liu, Shiyun; Wu, Xiongting; Zou, Guofa; Liu, Chunli; et al.
Abstract : Background and Purpose: Tetramethylpyrazine (TMP) was originally isolated from the traditional Chinese herb ligusticum and the fermented Japanese food natto and has since been synthesized. TMP has a long history of beneficial effects in the treatment of many cardiovascular diseases. Here we have evaluated the therapeutic effects of TMP on pulmonary hypertension (PH) in animal models and in patients with pulmonary arterial hypertension (PAH) or chronic thromboembolic pulmonary hypertension (CTEPH). Experimental Approach: Three well‐defined models of PH ‐chronic hypoxia (10% O2 )‐induced PH (HPH), monocrotaline‐induced PH (MCT‐PH) and Sugen 5416/hypoxia‐induced PH (SuHx‐PH) ‐ were used in Sprague‐Dawley rats, and assessed by echocardiography, along with haemodynamic and histological techniques. Primary cultures of rat distal pulmonary arterial smooth muscle cells (PASMCs) were used to study intracellular calcium levels. Western blots and RT‐qPCR assays were also used. In the clinical cohort, patients with PAH or CTEPH were recruited. The effects of TMP were evaluated in all systems. Key Results: TMP (100 mg·kg −1 ·day −1 ) prevented rats from developing experimental PH and ameliorated three models of established PH: HPH, MCT‐PH and SuHx‐PH. The therapeutic effects of TMP were accompanied by inhibition of intracellular calcium homeostasis in PASMCs. In a small cohort of patients with PAH or CTEPH, oral administration of TMP (100 mg, t.i.d. for 16 weeks) increased the 6‐min walk distance and improved the 1‐min heart rate recovery. Conclusion and Implications: Our results suggest that TMP is a novel and inexpensive medication for treatment of PH. Clinical trial is registered with www.chictr.org.cn (ChiCTR‐IPR‐14005379).